Temporal trends in incidence of Type 1 diabetes between 1986 and 2006 in Brazil - Negrato, C. A.; Dias, J. P. L.; Teixeira, M. F.; Dias, A. [UNESP]; Salgado, M. N. [UNESP]; Lauris, J. R. [UNESP]; Montenegro, R. M.; Gomes, M. B.; Jovanovic, L. (Editrice Kurtis S R L, 2010)
Background: Scarce information is available about the variation in the incidence of Type 1 diabetes in the Brazilian population in the last decades. Aim: The objective of this study was to assess the long-term trends (1986-2006) in the incidence of Type 1 diabetes in Bauru, São Paulo State, Brazil. Subjects and methods: The annual incidence of Type 1 diabetes (per 100,000 per yr) from 1986 to 2006 was determined in children yr of age, using the capture and recapture method. Results: A total of 176 cases were diagnosed in the study population. The overall incidence was 10.4/100,000 with a range of 2.82/100,000 in 1987 to 18.49/100,000 in 2002 representing a 6.56-fold increase within the same population. The estimated incidence, using the capture and recapture method varied from 2.82/100,000 per yr in 1987 to 27.20/100,000 per yr in 2002, representing a 9.6-fold variation. The global pattern of incidence variation was categorized as high (10-19.99/100,000 per yr), and very high (20/100,000 per yr) in 71.43% of the study-years. Incidence was slightly higher among females, Caucasians, children in the 5-9 yr of age range and belonging to lower socio-economic classes. Most diagnoses were established during the colder months and/or with higher pluviometric indexes. Conclusions: The incidence of Type 1 diabetes in children is increasing in Bauru, São Paulo State, Brazil, and the global pattern of incidence was classified as high or very high, mainly in the last 10 yr. All Brazilian regions should be involved in the study. (J. Endocrinol. Invest. 33: 373-377, 2010) (C)2010, Editrice Kurtis
Keywords: Brazilian population; children; incidence; risk factors; Type 1 diabetes